2021
DOI: 10.1186/s42408-021-00120-5
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for winter prescribed burning in mixed conifer plantations of the Sierra Nevada

Abstract: Background Young, planted forests are particularly vulnerable to wildfire. High severity effects in planted forests translate to the loss of previous reforestation investments and the loss of future ecosystem service gains. We conducted prescribed burns in three ~35-year-old mixed conifer plantations that had previously been masticated and thinned during February in order to demonstrate the effectiveness of winter burning, which is not common in the Sierra Nevada, California. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…Factors affecting fire behavior in young conifer stands are markedly different than in mature stands (Weatherspoon and Skinner, 1995;Lyons-Tinsley and Peterson, 2012), and applying standard burn prescriptions developed for mature stands may not be successful. Nonetheless, studies have shown that fire can be applied in stands as young as 15 years old (Peterson et al, 2007;Kobziar et al, 2009;Knapp et al, 2011;Reiner et al, 2012;Bellows et al, 2016;York et al, 2021). Lastly, whether sites have become marginal or unable to support forests under current or near future environmental conditions is an important consideration given changing climate and disturbance regimes.…”
Section: What Approaches To Reforestation Can Foster Resilience To Cl...mentioning
confidence: 99%
“…Factors affecting fire behavior in young conifer stands are markedly different than in mature stands (Weatherspoon and Skinner, 1995;Lyons-Tinsley and Peterson, 2012), and applying standard burn prescriptions developed for mature stands may not be successful. Nonetheless, studies have shown that fire can be applied in stands as young as 15 years old (Peterson et al, 2007;Kobziar et al, 2009;Knapp et al, 2011;Reiner et al, 2012;Bellows et al, 2016;York et al, 2021). Lastly, whether sites have become marginal or unable to support forests under current or near future environmental conditions is an important consideration given changing climate and disturbance regimes.…”
Section: What Approaches To Reforestation Can Foster Resilience To Cl...mentioning
confidence: 99%
“…Recent research on burn day windows in the Lake Tahoe basin suggested that increasing availability of specialized fire personnel in the fall and spring and adjusting prescriptions to burn more in the spring might be necessary to substantially increase burning (Striplin et al 2020). An even more recent analysis (York et al 2021) at the Blodgett Forest Research Station, to the west of Lake Tahoe, suggested that burning opportunities would be even narrower than Striplin et al (2020) had indicated, particularly because larger prescribed understory burns would require longer windows of dry fuels to be successful. In contrast, pile burns can be completed even under relatively wet conditions when the residual materials are kept dry under plastic sheets (Aurell et al 2017).…”
Section: Challenges With Increasing Burningmentioning
confidence: 99%
“…In contrast, pile burns can be completed even under relatively wet conditions when the residual materials are kept dry under plastic sheets (Aurell et al 2017). Additional research may be warranted to evaluate potential effects of conducting more burning in winter and spring, since such practices have not been widely studied and air quality may also be a constraint in the winter (York et al 2021).…”
Section: Challenges With Increasing Burningmentioning
confidence: 99%
“…This is particularly challenging for managers, since it suggests that the conventional tools available for managing young stands -planting and thinning-may be insufficient to protect them from highseverity fires. While it is possible to conduct prescribed fires in planted forests after several decades to effectively reduce fuels with very little tree mortality (York et al 2021a), conducting fires even earlier and with a high frequency that is aligned with the disturbance regime could be an unconventional approach that helps reduce wildfire severity and allows young stands to develop to maturity (North et al 2019). In mature stands that have not yet burned with high severity wildfires, shifting silviculture away from even-aged systems and toward gap-based systems that broadly reduce surface fuels while regenerating shade intolerant species may also reduce wildfire severity.…”
Section: Introductionmentioning
confidence: 99%